2020
DOI: 10.3390/ani10091538
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Causes in Free-Ranging Eurasian Brown Bears (Ursus arctos arctos) in Spain 1998–2018

Abstract: This work summarizes the mortality cases of twenty-five free-ranging Eurasian wild brown bears (Ursus arctos arctos) from the Cantabrian mountain range submitted for necropsy in Asturias and Castilla y León (northwestern Spain) from 1998 to 2018. Mortality cases were classified both caused by (i) “non-human intervention” or “human intervention” causes and based on (ii) “non-infectious” or “infectious” etiology. In four cases (16%) it was not possible to determine the cause of death due to the inadequate preser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Recently, C septicum was reported in a single wild brown bear after muscle damage, similar to other clostridial infections, such as C sordellii, C bifermentans, C chauvoei and C novyi. [1][2][3] Evidence of C septicum in a wild black bear (Ursus americanus) was associated with the immobilisation, just as in the present case in which C septicum is reported for the first time in a captive brown bear. 3 The aim of this report was to make veterinarians who work with zoo and wildlife animals aware of the fact that secondary bacterial infections after immobilisation can lead to death of Ursidae, with death occurring as early as 48 hours after infection with C septicum.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Recently, C septicum was reported in a single wild brown bear after muscle damage, similar to other clostridial infections, such as C sordellii, C bifermentans, C chauvoei and C novyi. [1][2][3] Evidence of C septicum in a wild black bear (Ursus americanus) was associated with the immobilisation, just as in the present case in which C septicum is reported for the first time in a captive brown bear. 3 The aim of this report was to make veterinarians who work with zoo and wildlife animals aware of the fact that secondary bacterial infections after immobilisation can lead to death of Ursidae, with death occurring as early as 48 hours after infection with C septicum.…”
Section: Introductionsupporting
confidence: 76%
“…Recently, C septicum was reported in a single wild brown bear after muscle damage, similar to other clostridial infections, such as C sordellii , C bifermentans , C chauvoei and C novyi . 1–3 Evidence of C septicum in a wild black bear ( Ursus americanus ) was associated with the immobilisation, just as in the present case in which C septicum is reported for the first time in a captive brown bear 3…”
Section: Introductionsupporting
confidence: 61%
“…Nevertheless, it seems that ICH is not a frequent cause of death in northwestern Iberian wolf populations, because the Asturian wolf population has recovered and maintained itself in recent decades (Blanco et al., 2008; García & Llaneza, 2012) and because we unaware of reports of clinical cases in the field. In contrast, a study of 21 brown bears in Asturias identified three that died of CAdV‐1, and all three animals showed clinical disease with consistent macroscopic and microscopic lesions (Balseiro et al., 2020; García Marín et al., 2018). Bears may be more vulnerable to severe infection and ICH, which could be related to their low genetic variability (García Marín et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The present study aimed to clarify the threat that CAdV‐1 may represent to bears and other carnivores by analysing the geo‐temporal distribution of CAdV‐1 in Asturias during a 10‐year period in wolves and to identify whether wolves may serve as a reservoir species that drives infections in bears and potentially other sympatric wild carnivores in the area. If so, wolves may be useful as CAdV‐1 sentinels because they can be sampled more easily than the endangered Cantabrian brown bear (Aguirre, 2009; Balseiro et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Brown bears are especially susceptible to infectious diseases because of the features of their populations (i.e., small and relatively isolated/fragmented), as well as their behavior and ecology (i.e., apex consumer and facultative scavengers) [ 10 ]. Recently, infectious diseases have been identified as an important cause of death in this population (39.7% in the period 1998–2023) [ 11 , 12 ]. The pathogens reported included Clostridium spp., verotoxigenic Escherichia coli , Canine Adenovirus type 1 (CAdV-1), and Canine Distemper Virus (CDV) [ [11] , [12] , [13] , [14] ].…”
Section: Introductionmentioning
confidence: 99%